2008
DOI: 10.1248/bpb.31.1434
|View full text |Cite
|
Sign up to set email alerts
|

Sequential and Quantitative Analysis of a Murine Model of Elastase-Induced Emphysema

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the serious causative diseases in death of aging people.1) Emphysema, one of COPD, is characterized as destruction of airway wall and small airway inflammation.1) An imbalance between elastinolytic proteases and their natural inhibitors is thought to play a role in the pathogenesis of emphysema. One animal model of emphysema is made by administrating of elastase into the lungs.2-4) Cigarette smoke-induced emphysema is another common model of emphysema. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…From this equation, it appears that the alveolar surface area per unit lung volume is proportional to 1/L m . Notably, the changes in alveolar surface area are closely related to the extent of tissue destruction and thus to the tissue density, as demonstrated from reported correlations between L m and lung mean density assessed with micro-CT in elastase murine model of emphysema (20). In MRI, information about tissue density can be obtained from the MR signal intensity variations induced by changes in proton spin density.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From this equation, it appears that the alveolar surface area per unit lung volume is proportional to 1/L m . Notably, the changes in alveolar surface area are closely related to the extent of tissue destruction and thus to the tissue density, as demonstrated from reported correlations between L m and lung mean density assessed with micro-CT in elastase murine model of emphysema (20). In MRI, information about tissue density can be obtained from the MR signal intensity variations induced by changes in proton spin density.…”
Section: Discussionmentioning
confidence: 96%
“…For each radial view, the k-space origin was acquired with a repetition time of 80 ms. The flip angle was set to 20 according to the Ernst angle condition, with an estimated lung T 1 value of 1600 ms (measurements not published). The minimum effective echo time was equal to 550 ms (the effective echo time is defined as the interval between the center of the radiofrequency pulse and the first data point of the acquisition) and was achieved with a gaussian-shape pulse excitation of duration of 0.4 ms and slice thickness of 1.7 mm.…”
Section: Mr Protocolmentioning
confidence: 99%
“…A single dose of elastase leads to airspace enlargement inducing emphysema-like lesions (Lucey et al 1998, Kononov et al 2001, Inoue et al 2003, Ishizawa et al 2004, Ito et al 2005, Kawakami et al 2008. In gen- Fig.…”
Section: Comparison Of Elastase Modelsmentioning
confidence: 99%
“…Kawakami and colleagues (2008) held a sequential and quantitative analysis using micro-computed tomography in a murine model of elastase emphysema, demonstrating the persistence of morphological changes up to four weeks after elastase instillation (Kawakami et al 2008). Other investigators have observed persistent elastase emphysema up to eight weeks and more after elastase instillation (Otto-Verbene et al 1992).…”
Section: Comparison Of Elastase Modelsmentioning
confidence: 99%
See 1 more Smart Citation